CREATING AND INVESTIGATION OF ADENOSINE-5-TRIPHOSPHATE LIPOSOMAL FORMS FOR ORAL APPLYING - O. V. Khrobatenko; N. V. Prytulska; S. M. Shulga (Biotechnologia Acta, 2013)
Liposomal form of adenosine-5-triphosphate (ATP) for oral applying was studied. The methods of obtaining and determining the size of the liposomes, the definition of ATP percentage content in liposomes were proposed. The effect of liposomal form of ATP on physical performance of laboratory animals by swimming to the limit of exhaustion was studied. It was shown that using of the liposomal form as compared with free ATP (in a similar dose) promoted the increased efficiency of laboratory animals. Application of liposomal form occurring at single administration for 6 days at a dose of 30 mg/kg facilated a 62% increase of efficiency, and 60 mg/kg did 76%, while consumption of liposomal form of ATP for 12 days did 64% and 93%, respectively.